Selected Issues from the Dark Side of the General Data Protection Regulation - Daniela Eva Cvik; Radka Pelikánová MacGregor; Michal Malý (Review of Economic Perspectives, 2018)
The Regulation (EU) 2016/679 on the protection of personal data (GDPR) was enacted in 2016 and applies from 25thMay 2018 in the entire EU. The GDPR is a product of an ambitious reform and represents a direct penetration of the EU law into the legal systems of the EU member states. The EU works on the enhancement of awareness about the GDPR and points out its bright side. However, the GDPR has its dark side as well, which will inevitably have a negative impact. Hence, the goal of this paper is twofold - (i) to scientifically identify, forecast, and analyze selected problematic aspects of the GDPR and its implementation, in particular for Czech municipalities, and (ii) to propose recommendations about how to reduce, or even avoid, their negative impacts. These theoretic analyses are projected to a Czech case study focusing on municipalities, which offers fresh primary data and allows a further refining of the proposed recommendations. An integral part of the performed analyses is also a theoretic forecast of expenses linked to the GDPR, which municipalities will have to include in their mandatory expenses and mid-term prognostic expectations regarding the impact on the budgets of these municipalities from Central Bohemia. The GDPR, like Charon, is at the crossing, the capacity and knowledge regarding its application is critical for operating in the EU in 2018. It is time both to admit that the GDPR has its dark side and to present real and practical recommendations about how to mitigate it.
Keywords: 330; Controller v. processor; Data protection officer; GDPR; Transparency